ANALYSIS OF ISLAMIC FINANCIAL LITERACY IN CONTROLLING IMPULSIVE BUYING BEHAVIOR IN GUNUNG LEUSER UNIVERSITY STUDENTS, ACEH - Gundahara, Gundahara; Andiansyah, Farma; Zulkarnaen, Dicky (IJMA (Indonesian Journal of Management and Accounting), 2025)
This research is motivated by the low level of Islamic financial literacy, the high tendency of impulsive buying that has the potential to cause waste, and the lack of interest of students in seeking references related to financial management. This study aims to analyze the effect of Islamic financial literacy on impulsive buying behavior in students of Gunung Leuser University, Aceh. Using a quantitative approach, this research is field-based with data collection methods through observation, interviews, documentation, and distributing questionnaires. Data analysis techniques include validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, simple linear regression, hypothesis tests, and determination coefficient tests (R²). The results of the study indicate that Islamic financial literacy has a significant effect on impulsive buying behavior with a positive relationship. Thus, the alternative hypothesis (Ha) is accepted, which indicates that Islamic financial literacy (X) has an effect on impulsive buying (Y). This is proven by the results of the regression test which shows a positive coefficient of 0.435 with a significance level of 0.000 (p < 0.05), which indicates that the higher a person's sharia financial literacy, the higher the tendency to make impulsive purchases.